Work-Life Balance and Work-Life Conflict : A Bibliometric Analysis - Rathi, Soni; Kumar, Praveen (Prabandhan: Indian Journal of Management, 2023)
Purpose : The primary focus of the study was to explore and provide a critical evaluation of work-life balance (WLB) and work-life conflict (WLC) literature and their publishing trends via bibliometric analysis. Methodology : The current analysis was based on a bibliometric analysis VOSviewer software, and through this, 449 articles were retrieved from the Scopus database covering the 2018–2022 time span. The following techniques of bibliometric analysis were used in this research: Citation analysis, cocitation analysis, and a thematic overview of WLB and WLC corpus (cooccurrence analysis). Additionally, coauthorship analysis was based on authors, institutions, and countries of published papers. Findings : The study’s findings unearthed the most essential and potent journals, the top cited authors, thematic structure, and five thematic clusters of WLB and WLC. It additionally rendered data of the prominent authors, journals, institutions, and nations that have shaped the previous review in this field of research. Originality : This analysis depicted that the concept is yet to be consumed, and more studies are still required to continue the analysis. Limitations and further recommendations were also highlighted in the current study.